Consideraciones pedagógicas sobre la comunidad educativa: el paradigma de la “escuela-educadora” - Martínez-otero Pérez, Valentín (Revista Complutense de Educación, 2006)
The question of relational nature in the educational institutions is usually passed over, except when cohabitation was considerably disturbed. In this case, the strengthening of the interrelationship scheme assumes in these pages a central value centered to pedagogical reflexions about the concept of educational community. We present practical keys around the model of a personalized educational community, and we criticize the approach of the learning organizations that learned, that is overvaluated nowaday for some sectors, and we reache by the analytical-comprehensive way the paradigm of the “educational-school”, genuine institution compromised with quality.